Nutritional Composition and Health Benefits of Teff (Eragrostis tef (Zucc.) Trotter) - Yoseph Asmelash Gebru; Desta Berhe Sbhatu; Kwang-Pyo Kim (Journal of Food Quality)
Teff (Eragrostis tef (Zucc.) Trotter) (Poaceae) is an annual crop with a very tiny grain. The crop is mainly cultivated in Ethiopia and Eritrea where it is used in preparing a pancake-like staple food called injera. Teff grain is the smallest of all whole flour grains in the world with a length of about 1.0 mm and a width of about 0.60 mm. The popularity of the crop is rapidly increasing throughout the world because of its attractive nutritional and functional properties. Thus, the crop is being successfully introduced and cultivated in many parts of the world including the USA, Canada, Australia, Switzerland, and the Netherlands. The growing global demand for the grain is due to its gluten-free nature, high level of essential amino acids (EAA), high mineral content, low glycemic index (GI), high crude fiber content, longer shelf life, and slow staling of its bread products compared to that of wheat, sorghum, rice, barley, and maize. The grain is linked to several health benefits including prevention and treatment of diseases such as celiac disease, diabetes, and anemia. These call for huge research opportunities to explore the nutritional and functional properties of the grain.